Profile of Environmental Knowledge and Attitudes Toward Environmental Care Among High School Students in Rural Areas - Fairuzzabadi Amrullah; Arum Setiawan; Indra Yustian; Hilda Zulkifli (Universitas Lambung Mangkurat, 2026)
Environmental education is an important foundation for developing students' ecological awareness, yet evidence on how biology instruction shapes environmental knowledge and environmental attitudes, particularly in Madrasah Aliyah (Islamic Senior High School) settings in Indonesia, is limited. Previous studies have shown that environmental knowledge does not automatically translate into pro-environmental attitudes, making it important to assess both dimensions simultaneously. This study employed a quantitative descriptive design with a sample of 80 students drawn from a population of 120 students at MA Nurul Jamil, using a validated Likert-scale questionnaire to measure two constructs: environmental knowledge and environmental attitudes. Results indicated that environmental knowledge was distributed across the categories of very good (11%), good (36%), sufficient (33%), and less good (20%), while environmental attitudes were concentrated in the categories of fair (56.25%), very good (13.75%), good (30%), and less good (0%), descriptively suggesting that attitude expression was not fully aligned with knowledge acquisition, although no inferential statistical analysis was conducted to confirm this relationship. These findings suggest that biology learning at MA Nurul Jamil has made a positive contribution to environmental awareness while highlighting the need for experiential and project-oriented learning strategies to bridge the gap between knowledge and attitudes; future research should employ correlational or regression analysis to examine this relationship more thoroughly.